1994
DOI: 10.1111/j.1600-051x.1994.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and clinical effects of metronidazole and amoxicillin in Actinobacillus actinomycetemcomitans associated periodontitis

Abstract: In this study, we evaluated the microbiological and clinical effects of mechanical debridement in combination with metronidazole and amoxicillin therapy in 48 patients with Actinobacillus actinomycetemcomitans‐associated periodontitis, 3 months and at least 24 months after active treatment. The results of this study showed that 47 out of 48 patients were still negative for A. actinomycetemcomitans subgingivally, at the mucous membranes, the tonsillar area and in the saliva, 2 years after therapy. The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
153
1
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 23 publications
13
153
1
5
Order By: Relevance
“…In the presence of a mouth or dental infection, antibiotics should be prescribed. The combination of amoxicillin and metronidazole represents the first-line therapy, especially with generalized aggressive periodontitis (47). In case of allergy or for patients receiving methotrexate as a disease-modifying agent, macrolides can be proposed.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of a mouth or dental infection, antibiotics should be prescribed. The combination of amoxicillin and metronidazole represents the first-line therapy, especially with generalized aggressive periodontitis (47). In case of allergy or for patients receiving methotrexate as a disease-modifying agent, macrolides can be proposed.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that A. actinomycetemcomitans still remained after debridement in a high proportion of sites initially infected with the bacteria (Christersson etal, 1985;Renvert etal, 1990). Some authors have shown that elimination can be achieved only by combining mechanical treatment with the use of antibiotics (Slots and Rosling, 1983;Pavicic et al, 1994).…”
Section: Actinobacillus Actinomycetemcomitansmentioning
confidence: 99%
“…The effectiveness of specific antibiotic types has been demonstrated for decades. For instance, an additional administration of amoxicillin and metronidazole has been proven to lead to a significant reduction in Aggregatibacter actinomycetemcomitans [11]. It follows, therefore, that the administration of various antibiotics would certainly be indicated in cases in which SRP alone does not produce the anticipated success due to persistent pockets or inaccessible points (e.g., furcation and concavities).…”
mentioning
confidence: 99%